Modelagem da circulação de um reservatório tropical polimítico - Rio, Cristina Maria Magalhães Granadeiro (Universidade Federal de São Carlos, 2003)
Environmental pulses occur very often in warm polymitic reservoirs and, together with shifts in the operational rules, lead to large internal temporal variability. The focus of this work was: (i) to evaluate the main characteristics and the complexity of physical processes during short-time events in a warm polymitic water body, Lobo (Broa) reservoir, and; (ii) to examine the potential of a hydrostatic three-dimensional (3D) numerical model at a coarse grid resolution to simulate correctly mixing and transport during short-time events in a warm polymitic reservoir. In this study we conducted two field experiments. In March-April 2001 a first collaborative field experiment, with intensive measurements that included both biological and physical processes, was realized in Lobo reservoir. During the 16 days experiment, a large spectrum of environmental conditions occurred: a storm, calm weather with moderate winds and the passage of a cold front. In May 2003 we conducted a second field experiment, also with intensive measurements, however focusing on the spatial variability of temperature and other variables in Lobo reservoir. A diurnal variation study was performed in both experiments. The 3D Estuary and Lake Computer Model was applied to modeling Lobo reservoir, S ao Paulo - Brazil, and was compared with data from both experiments. The reservoir spatial heterogeneity and rapid response to various pulses and diel patterns of heating and cooling were well reproduced by the numerical model. Thus, this can be a valuable tool for understanding evolution of the thermodynamics in a warm polymitic reservoir. Finally, in this work we highlight few inherent characteristics of polymitic reservoirs, which were found to be very important for the establishment of monitoring plans and the reservoir management.
Keywords: Hidrodinâmica; Limnologia; Modelo numérico; Broa, Represa do (SP); Experimentos de campo; CIENCIAS BIOLOGICAS::ECOLOGIA